Safety study, anti-inflammatory and antioxidant action of drug caramel with polyhexamethylene guanidine phosphate - Kurinnyi, A. V.; Belenichev, I. F.; Hladyshev, V. V.; Курiнний, Антон Валерiйович; Бєленічев, Ігор Федорович; Гладишев, Віталій Валентинович (Medip Academy, 2016)
Background: Among the new antiseptic medicines, most meeting modern requirements in terms of treatment of microbial invasion are one of the leading positions occupied by the polymeric guanidine compound. Polyhexamethylene guanidine phosphate (PHMGP) has a wide spectrum of antimicrobial activity and practical absence of toxicity. We have developed a new dosage form caramel “Guamel'” with the active pharmaceutical ingredient. Methods: on white rats of both sexes were studied parameters of acute toxicity and irritant dosage form caramel “Guamel'”, as well as anti-inflammatory and antioxidant effects. Results: It was found that the PHMGP developed drug caramel does not have skin-resorptive and allergenic action. Study of acute toxicity on white rats showed harmlessness studied dosage form PHMGP. It was found that a single oral administration to laboratory animals in drug caramel maximum allowable amount and cutaneous application does not lead to death during a 48 hour period of observation, does not cause visible changes in the basic physiological processes and does not affect the function of vital organs. On carrageenan model of inflammation it proved that the drug caramel with PHMGP exhibits anti-inflammatory effect, such a superior drug-referent "Septolete". It is also found to have developed in preparation of antioxidant activity in the inhibition of oxidative protein modifications also significantly superior to the reference drug. Conclusions: The developed dosage form caramel “Guamel'” for external use of the safety performance meets the requirements for such drugs. The developed dosage form caramel “Guamel'” exhibits high anti-inflammatory and antioxidant activity, which is the force exceeds the reference value. All of this is experimental rationale for the industrial production of this dosage form caramel “Guamel'”.
Keywords: PHMGP; Dosage form caramel guamel; Acute toxicity; Irritating; Anti-inflammatory and antioxidant activity